Preliminary Analysis of Slope Stability in Kuok and Surrounding Areas - Putra, Dewandra Bagus Eka; Choanji, Tiggi (UIR PRESS, 2016)
The level of slope influenced by the condition of the rocks beneath the surface. On high level of slopes, amount of surface runoff and water transport energy is also enlarged. This caused by greater gravity, in line with the surface tilt from the horizontal plane. In other words, topsoil eroded more and more. When the slope becomes twice as steep, then the amount of erosion per unit area be 2.0 - 2.5 times more. Kuok and surrounding area is the road access between the West Sumatra and Riau which plays an important role economies of both provinces. The purpose of this study is to map the locations that have fairly steep slopes and potential mode of landslides. Based on SRTM data obtained,  the roads in Kuok area has a minimum elevation of + 33 m and a maximum  + 217.329 m. Rugged road conditions with slope ranging from 24.08 Â° to 44.68 Â° causing this area having frequent landslides. The result of slope stability analysis in a slope near the Water Power Plant Koto Panjang, indicated that mode of active failure is toppling failure or rock fall and the potential zone of failure is in the center part of the slope.